(untitled) (The Batuk, 2023)
This article attempts to delineate the Greco-Roman history of rhetoric in light of the concept of ‘substance’. It examines how Greco-Roman Rhetoric, while traveling from Plato to Aristotle to Cicero to Quintilian, encounters debates and dialogues regarding the issues of essence, meaning, and purpose of rhetoric. Therefore, this article does a qualitative textual analysis of five texts: Phaedrusorgias by Plato (2002, 1864), On Rhetoric by Aristotle (n.d.), Oratory and Orators by Cicero (1875), and Institutio Oratoria by Quintilian (2013). In order to unravel the journey of Greco-Roman rhetorical substance, these texts have been analysed and interpreted from three different points of view: substance in rhetoric/oratory, substance in the language of rhetoric/oratory, and substance in rhetoricians/rhetor/orator. The article concludes that in the history of Greco-Roman rhetoric, Plato nullifies substance, Aristotle adds substance, Cicero amplifies substance, and Quintilian multiplies substance. The article not only tracks the history of Greco-Roman rhetoric from the perspective of substance but also opens new avenues for further research.